Evaluating the effect of aging on interference resolution with time-varying complex networks analysis - Ariza, Pedro; Solesio-Jofre, Elena; Martínez, Johann H.; Pineda-Pardo, José A.; Niso, Guiomar; Maestú, Fernando; Buldú, Javier M. (Frontiers in Human Neuroscience, 2015)
In this study we used graph theory analysis to investigate age-related reorganization of functional networks during the active maintenance of information that is interrupted by external interference. Additionally, we sought to investigate network differences before and after averaging network parameters between both maintenance and interference windows. We compared young and older adults by measuring their magnetoencephalographic recordings during an interference-based working memory task restricted to successful recognitions. Data analysis focused on the topology/temporal evolution of functional networks during both the maintenance and interference windows. We observed that: a) Older adults require higher synchronization between cortical brain sites in order to achieve a successful recognition, b) The main differences between age groups arise during the interference window c) Older adults show reduced ability to reorganize network topology when interference is introduced, and d) Averaging network parameters leads to a loss of sensitivity to detect age differences.